Vegetable oils as a source of functional ingredients - Kobets (Zadorozhnia), Elena; Arpul (Oleksiichuk), Oksana; Dotsenko, Viktor (My University, 2016)
Vegetable oils are unique pit health, they stimulate metabolic processes, used to treat cardiovascular diseases, diseases of the central and peripheral nervous system, obesity, anemia, allergic reactions, which is why their conduct in the product as a functional ingredient useful in physiologically significant amounts that will enhance the biological value of the product and will not lead to a deterioration in the organoleptic and physico-chemical characteristics of it.
Keywords: жиророзчинні вітаміни; fat-soluble vitamins; олії рослинні; vegetable oils; кафедра готельно-ресторанної справи